Pengaruh Variasi Produk Dan Lokasi Usaha Terhadap Minat Beli Konsumen Di Pasar Relokasi Studi Kasus Pasar Roga Berastagi - Karo, Immanuel Karo; Nst, Amrin Mulia Utama (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research aims to investigate the influence of product variation and business location on consumer purchasing interest in Berastagi’s Relocated Market, Roga Market. Product variation and business location are identified as potential factors influencing consumer preferences and understanding the dynamics of the local market. Using a quantitative approach with a survey research design, the sample was selected from visitors to Berastagi Market Center using stratified random sampling. Data were collected through questionnaires covering questions related to product variation, business location, and consumer purchasing interest. The findings of this research are expected to provide in-depth insights into the factors influencing consumer purchasing interest in traditional markets. The results indicate that product variety has a positive and significant effect on consumer purchasing interest, with a regression coefficient of 0.224 and a p-value less than 0.05. In contrast, business location does not show a significant effect on consumer purchasing interest, with a regression coefficient of -0.021 and a p-value greater than 0.05. The F-test shows that, simultaneously, product variety and business location have a significant effect on consumer purchasing interest, with an F-value of 6.684 and a p-value of 0.002.